2021
DOI: 10.1002/mdc3.13262
|View full text |Cite|
|
Sign up to set email alerts
|

Progression in Parkinson's Disease: Variation in Motor and Non‐motor Symptoms Severity and Predictors of Decline in Cognition, Motor Function, Disability, and Health‐Related Quality of Life as Assessed by Two Different Methods

Abstract: Background Parkinson's disease (PD) is multi‐symptom disease with variable progression. Objectives We performed a longitudinal study to address the evolution of motor symptoms (MS) and non‐motor symptoms (NMS), predictors of motor‐, cognitive‐, disability‐, and health‐related quality of life (HRQL) status and the relative usefullness of a battery of separate NMS scales (BSS) versus the Non‐Motor Symptom Scale (NMSS). Methods Seventy‐two patients were assessed at baseline and 4 years later with the NMSS and BSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 31 publications
3
17
0
Order By: Relevance
“…However, other longitudinal studies examining cognitive decline have reported similar attrition rates: 50% after 5 years, 45 and 46% after 4 years. 46 Patients in our sample lost to follow-up were older and had more severe motor and cognitive impairments, similar to previous reports. 46 The number of patients with cognitive IADL impairment was not different between patients who dropped out compared to those who were included, suggesting presence of cognitive IADL impairment did not impact attrition.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, other longitudinal studies examining cognitive decline have reported similar attrition rates: 50% after 5 years, 45 and 46% after 4 years. 46 Patients in our sample lost to follow-up were older and had more severe motor and cognitive impairments, similar to previous reports. 46 The number of patients with cognitive IADL impairment was not different between patients who dropped out compared to those who were included, suggesting presence of cognitive IADL impairment did not impact attrition.…”
Section: Discussionsupporting
confidence: 91%
“…46 Patients in our sample lost to follow-up were older and had more severe motor and cognitive impairments, similar to previous reports. 46 The number of patients with cognitive IADL impairment was not different between patients who dropped out compared to those who were included, suggesting presence of cognitive IADL impairment did not impact attrition. There was also a variable length in time to follow-up; however, as the FAQ Q groups had similar mean intervals, we infer that time to follow-up did not have a significant effect on our results.…”
Section: Discussionsupporting
confidence: 91%
“…Despite these efforts, few variables have been shown to be strong predictors of motor or cognitive decline in PD, and even fewer have been shown to predict both. [41][42][43] The current study suggests that in patients with PD, a simple screening question from the diagnosing clinician at the initial visit, asking about their nightly dream experiences, could identify patients at substantially higher risk for motor and cognitive deterioration in the near future. Furthermore, dream content alterations are easily recognized by the patient, unlike RBD, in which half of the affected patients are unaware of their DEBs.…”
Section: Discussionmentioning
confidence: 91%
“…In line with this, several studies have aimed to predict motor and cognitive progression in PD using complex machine‐learning algorithms 41 or clinical and nonclinical tests that can cumulatively take hours to administer 42 or may be invasive. Despite these efforts, few variables have been shown to be strong predictors of motor or cognitive decline in PD, and even fewer have been shown to predict both 41–43 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we cannot determine which NMS contributed most to disease burden and when they are actually most impactful, as previously reported. [28][29][30][31] This report provides a comprehensive summary of the differences in the occurrence of NMS between people with and without PD. We show that the prevalence and emergence of many NMS in PD are greater than expected from aging alone.…”
Section: Discussionmentioning
confidence: 99%